2017
DOI: 10.18535/jmscr/v5i11.120
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Myofascial Release Technique in Comparison with Passive Stretching in Reducing Spasticity in children with Cerebral Palsy*

Abstract: df=1,p = 0.002

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Passive stretching was included in the one of study to cerebral palsy patient. 26 In one of the article, stretching by resting hand splint was given to finger flexors in chronic hemiparetic patients for four weeks. 16 There were two studies done which examined the immediate effect of single session of muscle stretching 20-30 minutes on hypertonic calf muscle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive stretching was included in the one of study to cerebral palsy patient. 26 In one of the article, stretching by resting hand splint was given to finger flexors in chronic hemiparetic patients for four weeks. 16 There were two studies done which examined the immediate effect of single session of muscle stretching 20-30 minutes on hypertonic calf muscle.…”
Section: Resultsmentioning
confidence: 99%
“…The study concluded based on the analysis of MAS, the passive stretching is superior than MFR. 26 All the articles which we reviewed included various outcome measures. Nine articles used MAS as an outcome measure for measuring grades of spasticity, five studies used PROM as an outcome measure, four studies used EMG parameters as an outcome measure and one article used a spatial temporal gait parameter.…”
Section: Resultsmentioning
confidence: 99%